Skrinning Status Gizi Remaja dan Upaya Pencegahan Anemia di SMK Perintis 29 - Widyaningsih, Ari; Isfaizah; Moneca Diah Listiyaningsih; Yulia Nur Khayati; Wahyu Kristiningrum (INDONESIAN JOURNAL OF COMMUNITY EMPOWERMENT (IJCE), 2023)
Iron deficiency anemia is estimated to be the single largest cause of morbidity and mortality in adolescents. Anemia that occurs can cause decreased reproductive health, motoric and mental development, hampered intelligence, decreased learning achievement, decreased fitness levels and not achieving maximum height. The results of interviews with the school principal and guidance and counseling teachers at SMK Perintis 29 showed that the problem currently faced by partners is that cases of anemia in adolescent girls have not been identified because Hb screening examinations have never been carried out which are known to be effective in identifying the incidence of anemia in adolescent girls. The solution to the problem is Hemoglobin screening to increase adolescent awareness about the importance of anemia and the factors that influence it. The anemia screening activity began with registration of 30 young female screen participants, followed by TB and BB checks, Hb and blood pressure checks. The results of the activity showed that all teenage girls in grades X and The next community service activity focuses on empowering students with adolescent anemia to increase adolescent diet knowledge and skills.   ABSTRAK                 Anemia defisiensi besi diperkirakan menjadi satu-satunya penyebab terbesar kesakitan dan kematian pada remaja. Anemia yang terjadi dapat menyebabkan menurunnya kesehatan reproduksi, perkembangan motorik, mental, kecerdasan terhambat, menurunnya prestasi belajar, tingkat kebugaran menurun dan tidak tercapainya tinggi badan maksimal. Hasil wawancara dengan kepala sekolah dan guru BK di SMK Perintis 29 didapatkan data bahwa masalah yang dihadapi mitra saat ini adalah belum teridentifikasinya kasus anemia pada remaja putri karena belum pernah dilakukan pemeriksaan skrinning Hb yang diketahui efektif mengidentifikasi kejadian anemia remaja putri. Solusi permasalahan yang dilakukan adalah skrinning Hemoglobin untuk meningkatkan kesadaran remaja tentang pentingnya anemia serta faktor yang mempengaruhinya. Kegiatan skrinning anemia dimulai dengan registrasi peserta skrinnin sebanyak 30 remaja putri, dilanjutkan dengan pemeriksaan TB dan BB, Pemeriksaan Hb dan tekanan darah. Hasil kegiatan didapatkan bahwa semua remaja putri kelas X dan XI (100 %) di SMK Perintis 29 mengikuti kegiatan screening, 8 diantaranya mengalami anemia dan sebanyak 10 remaja berstatus gizi kurus. Kegiatan pengabdian masyarakat selanjutnya berfokus pada pemberdayaan siswa dengan anemia remaja untuk meningkatkan pengetahuan dan ketrampilan diet remaja.